Real Time PCR detection of Macrobrachium rosenbergii (de Man, 1879) larvae with emphasis to their ecology - Harikrishnan Mahadevan; Jose Deepak; Nidhin B.; Anilkumar K.P. (Aquatic Living Resources, 2021)
Species specific identification of early larval stages of many decapod crustaceans sampled from plankton collections remains cumbersome owing to lack of distinguishable characteristics, where DNA based molecular methods provide accurate results without taxonomic ambiguities. In the present study, an attempt was made to detect temporal occurrence of early zoea of freshwater prawn Macrobrachium rosenbergii (de Man) using real-time PCR assays in polyhaline, mesohaline and oligohaline areas of a tropical positive estuary, the Vembanad lake (S. India). High caridean larval abundance could be recorded in polyhaline areas in all seasons while it could be recorded in monsoon season in mesohaline and oligohaline areas. 113 DNA isolations were successfully made from morphologically identified taxonomic units (MOTU) and SYBR Green based RT-PCR amplifications using designed primer for M. rosenbergii yielded positive detections in 38 samples (34%) representing all seasons in all three zones. Positive detections could be recorded in all months except May in mesohaline areas and differed significantly (F = 17.2 p < 0.01) with the same in polyhaline and oligohaline areas. The present results of molecular detection of M. rosenbergii larvae extend confirmation of its breeding ground in Vembanad lake where appropriate management strategies could be enforced for stock conservation of this species.